The good, the bad, and the mediocre: Moller, AT (ed) (1995) Perspectives on personality. Durban: Butterworths. ISBN 0 409 10928 2. - Gillmer, Bruce (PINS-Psychology in Society, 2026)
There is a genre of Westerns that has always pleased me enormously. Like this text has. There were mostly good ous, some of whom turned nasty, a few bad from the outset, and always one ugly. It is, I believe, the first text on personality theory by South African psychologists in the English language. The contributors are all Afrikaner academics. The intended reader is likely to be an undergraduate at an English campus who is increasingly likely to be "non-European", or that New South African student, the black English second-language student at an Afrikaans university. All well and good so far.